Standardization of Technique cultivation of Tricholoma giganteum massee in Kerala - P.R.Prathibaha (Department of Plant Pathology, College of Agriculture, 2013)
The present investigation on “Standardization of techniques for cultivation of Tricholoma giganteum (Massee) in Kerala” was conducted at the Department of Plant Pathology, College of Agriculture, Vellayani, during 2012-2013. The aim of the study was to explore the possibility of cultivation of Tricholoma giganteum (Massee) on readily available cheap substrates and to develop a package for commercial cultivation in Kerala.